DIGITAL MICRO-ENTREPRENEURSHIP AND LOCAL INNOVATION SYSTEMS FOR ADVANCING VILLAGE ECONOMIC GROWTH - Ikhsan Nendi (Politeknik Siber Cerdika Internasional, 2025)
This research investigates digital micro-entrepreneurship in rural areas through the local innovation systems framework. Addressing limited formal employment, seasonal agricultural income, and digital divides, this study examines how smartphone platforms create market pathways while raising concerns about uneven value capture and exclusion. The study maps the entrepreneur typology, explains how digital technologies reshape the dynamics of the innovation system, and identifies constraints that affect the quality and sustainability of entrepreneurship. Employing qualitative case study methodology, data were collected through interviews, focus groups, and system actor mapping from January to December 2024. Three villages were selected: Village A (peri-urban, strong connectivity), Village B (agricultural, moderate connectivity), and Village C (remote, unreliable). Among 45 identified micro-entrepreneurs, 60% are women aged 25-40. Findings reveal social selling ecosystems dominate, with hybrid online-offline models prevailing due to trust and payment preferences. Digitalization accelerates knowledge flows through trans-local learning and enables partial institutional evolution, most effectively in digitally-advantaged villages. However, the lack of formal financial records constrains assessment. Digital tools catalyze rural innovation system reconfiguration, but benefits remain mediated by digital literacy, capital access, and social support. Implications emphasize tiered policy formalization, cooperative digital infrastructure, and targeted financial inclusion. Study limitations include a small sample (45 entrepreneurs from 3 villages), a geographic focus on 1 district, self-reported data, and a 12-month time frame.